2017
DOI: 10.1332/239788217x14866284542346
|View full text |Cite
|
Sign up to set email alerts
|

Family care work: a policy-relevant research agenda

Abstract: This article addresses the need for policy-relevant research agendas on family care in transaction with formal care and public as well as organisational norms and policies in light of the crisis in caregiving for older adults. We propose a combined institutional and life-course theoretical approach, suggesting seven ways of organising scholarly enquiry to promote understanding of the changing nature of family care in the 21st century, inform policymakers’ efforts at supporting family caregivers and improve car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…For instance, recent work in the United States has found that providing care for a parent in midlife is associated with a reduction in women's wages but not men's wages (Glauber 2019). More research is needed to understand the nexus of individual, family, and structural influences on caregiving (Moen and DePasquale 2017) given that welfare state programs, like cash benefits paid to seniors, often influence women's participation in care but not men's (Haberkern, Schmid, and Szydlik 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recent work in the United States has found that providing care for a parent in midlife is associated with a reduction in women's wages but not men's wages (Glauber 2019). More research is needed to understand the nexus of individual, family, and structural influences on caregiving (Moen and DePasquale 2017) given that welfare state programs, like cash benefits paid to seniors, often influence women's participation in care but not men's (Haberkern, Schmid, and Szydlik 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For middle-age adults who are near retirement, having more caregiving responsibilities may delay or forgo their ability to retire, potentially impacting the caregivers' own financial well-being at the end of their life. In addition, understanding multigenerational care and gender differences has important implications for assessing family care needs in workplace and country-or state-level policies (Moen and DePasquale 2017). A recent study estimates that the cost to replace informal caregiving of older family members with formal care would be over $17,000 year in the United States (Cecchini 2018); this cost would only be larger for those giving to multiple family members at once.…”
Section: Discussionmentioning
confidence: 99%
“…Even under normal conditions, the stresses of caregivingin addition to those of formal workforce participationcan be harmful for health and wellbeing, especially among the women who inordinately bear those responsibilities (Moen & DePasquale, 2017;Schulz, 2020). In fact, a long-standing literature has illustrated a multitude of negative consequences for caregivers, even including increased risk of mortality (Schulz & Beach, 1999).…”
Section: Caregiving and Covid-19mentioning
confidence: 99%
“…We recommend that policy makers keep in mind that families and public health go hand-in-hand, and that policies aimed at workers, caregivers, and older adults can help advance life expectancy and reduce health inequities (Moen & DePasquale, 2017;Schulz, 2020). In such cases, the more universal and accessible these policies are, the more likely they are to benefit caregivers and families in need (e.g., Herd & Moynihan, 2019).…”
Section: Moving Forward: Policy Implications For Family Caregiversmentioning
confidence: 99%
“…Besides childcare and housework, family care is an important aspect of unpaid work (Bianchi et al, 2012; ILO, 2018; Kröger & Yeandle, 2014). Throughout this article, the term ‘family care’ refers to the activities of individuals who care for a family member in regular need of care due to poor health, disability, or age-related frailty (Kröger & Yeandle, 2014; Moen & DePasquale, 2017). Typical childcare is not subsumed under the concept of family care used in this article, while exceptional childcare is (Daly, 2001; Kröger & Yeandle, 2014; Stewart, 2013).…”
Section: Introductionmentioning
confidence: 99%